Konsep Qanaah Sebagai Media Terapi Fomo Syndrom Menurut Quraish Shihab Dalam Tafsir Al-Mishbah - Siti Asyiyah Nurhidayati; M. Irfan Riyadi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
The phenomenon of Fear of Missing Out (Fomo) Syndrome on social media is currently a relevant issue. Fomo can affect everyone, from teenagers to adults, who actively use social media. Fomo, as a social anxiety characterized by the fear of missing out on experiences that others have, has become a significant issue in the digital era. This study aims to explain the concept of qanaah described by Quraish Shihab in Tafsir Al-Mishbāh as a therapeutic medium for the phenomenon of Fear of Missing Out (Fomo) Syndrome. This study uses a qualitative-based research type (Library Research) with a descriptive analysis approach. The data collection method used by the researcher uses a documentation study, which takes references from several literatures such as books, journals, tafsir books, articles and other relevant literature. The collected data is processed and analyzed using a descriptive analysis method, namely by explaining Quraish Shihab's interpretation systematically. The results of this study indicate that 1). According to Quraish Shihab, qanaah, which is interpreted as a sense of sufficiency and satisfaction with what is owned, offers an alternative perspective in dealing with social pressures and consumerism that trigger Fomo. This concept emphasizes the importance of self-acceptance, gratitude. As stated in Qs. Al-Baqarah (2) verses 207, 152, Qs. Ibrahim (14) verses 7, 43, Qs. At-Taubah (9) verse 59, Qs. Yusuf verse 20 and Qs. Al-Hajj verse 36. By internalizing qanaah, a person can reduce anxiety related to the loss of experience and build a healthier psychological balance. 2). This qanaah concept can be an effective therapy media to overcome Fomo Syndrome. by instilling an attitude of consent, gratitude and asceticism.